POTENSI OBYEK WISATA ALAM AIR TERJUN ENTOBA DI DESA NYANGGAI KECAMATAN PINOH SELATAN KABUPATEN MELAWI - Saputra, Oky Wahyu; Siahaan, Sarma; Widiastuti, Tri (Universitas Tanjungpura, 2021)
Â Assessment of natural tourist attraction objects is a systematic and balanced process or activity to collect information about everything that is unique and has high attractiveness value for tourists who come to a certain place and area. This study aims to obtain the value of tourism objects in Nyanggai Village, South Pinoh District, Melawi Regency, West Kalimantan Province, especially for natural tourism of Entoba Waterfall. The method used in this study is a survey method with interview techniques and the tool used in data collection is a questionnaire. The results of the calculation of each assessment criteria based on the 2003 ODTWA PHKA development standard, the assessment of each criterion obtained an average value of 269.14. Entoba waterfall area gets a bad score (C) which means the Entoba waterfall area is not potential to be developed as a natural tourist spot. The local government is expected to optimally assist and facilitate the community in planning the development and management of the natural attractions of Entoba Waterfall as well as increasing access to locations and other facilities intensively to the existence of Entoba Waterfall, both formally and informally.Keywords: Entoba Waterfall, Nyanggai Village, Potential Natural Tourism Objects.AbstrakPenilaian obyek daya tarik wisata alam adalah suatu proses atau kegiatan yang sistematis dan seimbang untuk mengumpulkan informasi tentang segala sesuatu yang unik dan bernilai daya tarik tinggi bagi wisatawan yang datang ke suatu tempat dan daerah tertentu. Penelitian ini bertujuan untuk mendapatkan nilai obyek wisata di Desa Nyanggai Kecamatan Pinoh Selatan Kabupaten Melawi Provinsi Kalimantan Barat khususnya untuk wisata alam Air Terjun Entoba. Metode yang digunakan dalam penelitian ini adalah metode survey dengan teknik wawancara dan alat yang digunakan dalam pengumpulan data adalah kuesioner. Hasil perhitungan setiap kriteria penilaian berdasarkan standar pengembangan ODTWA PHKA 2003, penilaian setiap kriteria diperoleh nilai rata-rata sebesar 269,14. Kawasan air terjun Entoba mendapat nilai buruk (C) yang berarti kawasan air terjun Entoba tidak potensial untuk dikembangkan sebagai tempat wisata alam. Pemerintah daerah diharapkan secara optimal membantu dan memfasilitasi masyarakat dalam merencanakan pengembangan dan pengelolaan objek wisata alam Air Terjun Entoba serta meningkatkan akses lokasi dan fasilitas lainnya secara intensif terhadap keberadaan Air Terjun Entoba, baik formal maupun informal.Kata Kunci : Air Terjun Entoba, Desa Nyanggai, Potensi Obyek Wisata Alam.